The commognitive perspective of teaching skills of prospective mathematics teachers in microteaching subjects - Moh Zayyadi; Toto Nusantara; Harfin Lanya (Universitas Hamzanwadi, 2022)
This study aims to describe the teaching skills of prospective mathematics education teachers in micro-teaching subjects from a commognitive perspective. This type of research is qualitative research. The research subjects consisted of 15 students of the 2015 Mathematics Education Study Program class, which were taking micro-teaching courses. The instrument used in this study was a rubric sheet—an assessment of prospective teachers' teaching skills. Data analysis techniques used are data reduction, data presentation, and conclusion collection. The results showed that: Prospective mathematics education teachers in preliminary activities often use the word usage component, visual mediator, routine and do not use the narrative component. In the core activities of learning mathematics, teacher candidates use four components commognitive, which are the use of words, visual mediators, routine, and narrative. In the selection of mathematics education, teacher candidates only use the word use component. Commognitive provides an overview of mathematical cognitive-communication and content in the learning carried out.